345 Blood pressure and autonomic function in essential hypertension: comparative evaluation of 24-hour heart rate variability and blood pressure. (8th December 2021) - Pivetti, Vanessa; Lazzeroni, Davide; Moderato, Luca; Centorbi, Claudio Stefano; Bini, Matteo; Brambilla, Lorenzo; Magnani, Giulia; Piepoli, Massimo; Ardissino, Diego; Niccoli, Giampaolo; Coruzzi, Paolo; Cabassi, Aderville
Abstract: Aims: Arterial hypertension (AHT) represents the leading cause of cardiovascular disease (CVD) and premature death worldwide. Essential AHT accounts for 95% of all cases of hypertension; although the aetiology of essential AHT is still largely unknown, a pivotal role of autonomic nervous system has been proposed and demonstrated. Both excessive sympathetic tone and vagal withdrawal, that define autonomic dysfunction, has been associated with essential AHT. The aim of our study was to investigate the relationship between blood pressure and autonomic function in essential hypertension; this was done comparing 24 h heart rate variability and 24 h blood pressure data, simultaneously collected, in a population of essential AHT subjects. Methods: A prospective registry of 179 consecutive not selected essential AHT patients were considered in the present study. All patients underwent cardiac evaluation at the Primary and Secondary Cardiovascular Prevention Unit of the Don Gnocchi Foundation of Parma. All subjects underwent 24 h ECG monitoring, and 24 h Ambulatory Blood Pressure Monitoring, during the same day. Twenty-four hours Heart Rate variability analysis included: Time-domain, frequency-domain and non-linear domain. Results: Mean age was 60 0a11.7 years, male gender was prevalent (68.4%). Among the population 26 (14.7%) subjects had diabetes; the prevalence of family history of CVD was 61.7% and 66.5% had dyslipidaemia; body mass index mean values were 27.6 7.4.3. In the whole population, the prevalence of uncontrolled AHT was 80.5%, divided into: 53.1% systo-diastolic, 17.9% isolated systolic, and 9.5% isolated diastolic. The prevalence of untreated AHT (recent diagnosis) was 40.2%, while treated AHT was 59.8% and only 19.6% had controlled blood pressure values (AHT at target). 12.3% of patients were treated with Beta Blockers. A significant correlations between diastolic blood pressure (DBP) values (24 h and day-time), LF/HF ratio (24 h) ( r  = 0.200; P  = 007) and DFA alfa1 (24 h) ( r  = 0.325; P  = 0.000), two know markers of sympathetic tone, were found. A higher sympathetic tone, expressed as high LF/HF, was found in isolated diastolic AHT compared to other types of AHT and the lowest sympathetic tone was found in isolated systolic AHT. Considering non-linear (complexity) analysis, DFA alfa1 (24 h) showed a significant correlation with DBP values that remained independent even after multiple adjustment for BMI, age, gender and Beta Blockers ( β  = 0.218; P  = 0.011). Moreover, the lack of DBP control was associated with high sympathetic tone (LF/HF 3.8 112.3 vs 5.5 .33.3; P  < 0.0001). On the other hand, no significant correlations between all DBP data and vagal markers, such as SDNN index, RMSSD and HF, were found. Again, no significant correlations between 24 h, daytime, night-time SBP and time or frequency HRV data as well as with non-linear (complexity) analysis were found. Finally, considering 'autonomic dipping', expressed as changes in HRV data between day and night, a strong inverse correlation between vagal markers and Heart Rate Dipping ( r  = −0.297; P  < 0.0001) was found; correlation that remain independent even adjusted for age, gender, BMI, and BB. On the other hand, no association between blood pressure dipping and autonomic dipping was found. Conclusion: Diastolic blood pressure and uncontrolled diastolic AHT, rather than systolic AHT, are associated with a hyper-sympathetic tone rather than with blunted vagal tone. The lack of heart rate dipping during night-time in AHT is associated with blunted vagal activation rather than a persistent night-time hyper-adrenergic tone.